Evaluation of the fat plane of the pancreatic groove using multidetector CT. Issue 10 (October 2018) - Silman, C.; Matsumoto, S.; Mori, H.; Yamada, Y.; Otsuka, A.; Hongo, N.; Ohta, M.; Inomata, M.; Takaki, H.; Fukuzawa, K.
Abstract : Aim: To assess the pancreatic groove fat plane in the normal population and compare this with the fat plane in patients with groove pancreatitis or carcinoma using multidetector computed tomography (CT). Material and methods: The pancreatic groove fat plane was evaluated retrospectively in 460 normal subjects (normal group), and in 25 patients with groove pancreatitis or carcinoma (pathology group) using 5 mm- and 1 mm-thick slices of unenhanced axial multidetector CT images. Two investigators independently assessed the degree of pancreatic groove fat plane visualisation using a four-point scale (grade 1: visualisation of 0–25%, grade 2: 26–50%, grade 3: 51–75%, grade 4: 76–100%). Pancreatic parenchymal condition, age, sex, body mass index, diabetes mellitus, and dyslipidaemia were also evaluated. Results: The interobserver agreement for the visualisation grades was almost perfect (k-value = 0.95). In the normal group, grade 4 visualisation of the pancreatic groove fat plane was more common in those aged >80 years (78.6%) compared with younger age groups. Pancreatic atrophy and fatty infiltration significantly improved fat plane visualisation. In the pathology group, grade 4 visualisation of the pancreatic groove fat plane was not seen in either groove carcinoma or pancreatitis. A cut-off point of ≤50% visualisation of the pancreatic groove fat plane showed 95% sensitivity and 82% specificity for detecting possible abnormalities in older patients (>60 years). The clinical factors investigated were not significantly related to pancreatic groove fat plane visualisation. Conclusion: Pancreatic groove fat plane visualisation could be a good predictor for detecting groove abnormalities. Highlights: There was a correlation between groove fat plane visualization and age. Other factor to influence groove fat plane was fatty pancreas and atrophy. Cut-off point of 50% groove visualization was useful for predicting abnormalities. This method provides high sensitivity especially in elder population.